Bahasa Inggris - Wijaya Salim, James; Nila Armelia Windasari (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
As frozen food retailers in Indonesia face mounting pressure from both economic challenges and competitive alternatives, strategic adaptation across different customer segments becomes increasingly essential. This research investigates the adaptive strategies of “FrozenMart” in addressing foot traffic fluctuations and enhancing customer engagement in both B2B and B2C markets. A mixed-methods approach was employed, including quantitative surveys across 10 branches (n=300) and qualitative inputs from stakeholders. The study explores product display preferences, promotional effectiveness, and membership adoption using descriptive statistics, importance-performance analysis (IPA), and K-Means clustering. Financial simulations were conducted using ROI, CPA, BEP, NPV, and IRR to assess strategic viability. Findings reveal a strong preference among B2C customers for categorized product displays and direct discount schemes. Although only 23.7% are members, over 90% acknowledge membership influence on purchasing behavior. B2B respondents emphasized the importance of delivery services and exclusive pricing. Hybrid strategies—bundling, segmented membership, and localized events—showed the highest ROI and consumer retention potential. The study highlights that personalized experience and localized engagement are key to sustaining competitiveness in Indonesia’s frozen food retail landscape.